2017
DOI: 10.1002/brb3.890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender, digit ratio, and menstrual cycle on intrinsic brain functional connectivity: A whole‐brain, voxel‐wise exploratory study using simultaneous local and global functional connectivity mapping

Abstract: IntroductionGender and sex hormones influence brain function, but their effects on functional network organization within the brain are not yet understood.MethodsWe investigated the influence of gender, prenatal sex hormones (estimated by the 2D:4D digit ratio), and the menstrual cycle on the intrinsic functional network organization of the brain (as measured by 3T resting‐state functional MRI (rs‐fMRI)) using right‐handed, age‐matched university students (100 males and 100 females). The mean (±SD) age was 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Since Iat and Inp are regarded as ‘cognitive’ impulsivity 24 , this study could successfully detect the difference in the pathophysiology between cognitive and motor impulsivity in PD. Although no study to date reported the association between ‘cognitive’ impulsivity and right FPN, the FPN plays an important role in instantiating and flexibly modulating cognitive control 25 , 26 . Therefore, our findings suggest that abnormal cognitive control due to dysfunction of FPN is related to ‘cognitive’ impulsivity in PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Iat and Inp are regarded as ‘cognitive’ impulsivity 24 , this study could successfully detect the difference in the pathophysiology between cognitive and motor impulsivity in PD. Although no study to date reported the association between ‘cognitive’ impulsivity and right FPN, the FPN plays an important role in instantiating and flexibly modulating cognitive control 25 , 26 . Therefore, our findings suggest that abnormal cognitive control due to dysfunction of FPN is related to ‘cognitive’ impulsivity in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Three runs, each with 105 volumes, were performed for each participant. In total, data were acquired over approximately 15 min during a resting state for each participant, as this duration was deemed the most appropriate to obtain reliable data 26,62 . The participants were asked to remain awake but keep their eyes closed during the acquisition.…”
Section: Mri Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used CompCor [ 31 , 32 ], six head motion time-course parameters regression [ 33 ], and global signal regression (mean time course of the functional brain image voxels) to exclude signal artefact unrelated to brain activity [ 34 36 ]. Temporal filtering (from 0.01 to 0.1 Hz) was then applied to remove constant offset and linear trends over each run.…”
Section: Methodsmentioning
confidence: 99%
“…Centrality analysis using rs-fMRI has detected alterations in the network in several epilepsy types 10 , 20 , 21 , and initial observations suggested a network disruption in epilepsy and disease progression as well as postsurgical seizure outcome, which emphasizes that graph theoretical analysis may lend markers for disease staging and prognostics. In this present study, we employed normalized α-centrality (nAC) on rs-fMRI 22 , 23 to quantify the brain regional network organization to compare different centralities. The nAC measures the strength of a node in a network from the local viewpoint to the global viewpoint by changing the parameter (that is, α) from zero to 1/λ; thereby, λ is the maximum eigenvalue of the adjacency matrix of the network.…”
Section: Introductionmentioning
confidence: 99%